Nationalism and Populism Expressions of Fear or Political Strategies? - Jacob, Frank; Schapkow, Carsten (De Gruyter, 2022)
Right wing populism has become an apparent and expanding phenomenon of the present. Nationalist claims to protect the state against waves of immigration are en vogue. Populists claim to secure national interests and to defend cultural values. The cultural Other is used to establish or to strengthen a narrative of fear. The proposed edited volume will examine the interrelationship of nationalism and populism during the 20th and 21st centuries.